Taxonomic studies on the genus Delphinium (Ranunculaceae) from China (XXV): D. jilongense and D. unifolium, another two new synonyms of D. himalayae, a species mainly occurring in Nepal but also in China (southern Xizang) - Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2023)
Based on consultation of literature and critical observations on herbarium specimens, we demonstrate that in addition to Delphinium subspathulatum (Ranunculaceae) and D. tabatae which we have previously reduced to the synonymy of D. himalayae, D. jilongense described from China’s southern Xizang (Gyirong) and D. unifolium described from Nepal are also conspecific with this eastern Himalayan species. We therefore place both of them in synonymy with D. himalayae herein.